Sorogan and Bandongan Traditions at Islamic Boarding Schools: Case study at Al-Arsyad Islamic Boarding School Metro Lampung - Anissatul Faqziaty; Siti Roudhotul jannah; Sucipto Sucipto; Anik Karimuloh (Journal of Research in Islamic Education, 2021)
This article aims at describing sorogan and bandongan as a tradition of teaching and learning in Islamic boarding school. Sorogan and bandongan have important role due to learning activities in Islamic boarding schools generally use both models. This research was case study where the data collected through an interview, observation and in-depth study on the literature relevant to the research problem. The data collected were then analyzed using an analytical model. The results of this study found that the main function of sorogan and bandongan is as a guide for learning. The characteristics of sorogan and bandongan are learning models that prioritize individual service approaches and collective services. This model is usually used by Kyai and santri in studying and translating the yellow book (classical book of ulama). The implications of this study are expected to encourage that sorogan and bandongan can be preserved and further developed as a learning system.